Acceptance of human rights by third world countries: Malaysia - Diana Peters (Universiti Malaysia Sabah, 2005)
Before the fateful 11 September 2001, human rights was among key issues being debated at the international level. With a global population of six billion and rising, the neglect of human rights, whether apparent or not, could not be avoided. These rights are the claims made on political authorities in which every human being is said to be entitled to. Many countries, particularly developing and Third World, believe that the laws protecting human rights are far from universal in nature. Rights are subject to numerous conditions present in the society of a given country, such as religion and culture. Modern thinking brings into focus three generations of rights; the first being broadly political, the second focuses on economic and social rights, and the third build on the rights of the people. This research seeks to determine why a number of Asian countries, particularly Malaysia, feel that the issue of human rights needs to be tailored to fit the specific needs of a given country. Particular attention would also be given to the Universal Declaration of Human Rights of 1948 and the extent to wish Malaysia has been willing to be party of the covenants.